The perceived effect of digital transformation and resultant empowerment on job performance of employees in the fitness family business - Yildiz, Kadir; Akoglu, Halil Erdem; Emir, Esra; Angosto, Salvador; Garcia-Fernandez, Jeronimo (Emerald Group Publishing Ltd, 2025)
PurposeThe impact of technological transformations in all sectors is undeniably significant, especially in fitness family business. The aim is to examine the digital transformation perceptions of fitness centre employees and the effects of perceived empowerment on their job performance in family business in Turkey.Design/methodology/approachThe sample was 334 fitness centre employees. Four variables were evaluated (digital transformation, meaning competence, self-determination and job performance), and PLS-SEM was used.FindingsThe digital transformation process in the fitness sector can be considered as an important factor in terms of creating new business ventures. Our results showed that digital transformation perceived by family business employees had a significantly influence on the meaning competence of the employees. Also, the meaning competence of employees was a mediator between the digital transformation and job performance.Practical implicationsManagers of family businesses must take into account that an appropriate digital transformation of their products and/or services has an impact on the meaning competence of their employees. Thus, through increased competence in employee performance, the digitization of family business fitness will lead to higher employee performance and productivity.Originality/valueThis study innovates by linking digital transformation as a factor influencing the coach's own motivation and self-perceived competence in the use of technology to their job performance.
Keywords: Digital Transformation; Sport Services; Perceived Empowerment; Digital Impact; Job Performance; Fitness Industry